2022
DOI: 10.1109/jstars.2022.3208955
|View full text |Cite
|
Sign up to set email alerts
|

NL-MMSE: A Hybrid Phase Optimization Method in Multimaster Interferogram Stack for DS-InSAR Applications

Abstract: When the distributed scatterer interferometric synthetic aperture radar (DS-InSAR) technology is used for surface deformation monitoring, the accuracy strongly depends on the quality of phase optimization. Especially in the low coherence region, how to conveniently and effectively improve the quality of phase optimization has been a hot and difficult research topic in recent years. This paper proposes a hybrid phase optimization method for the DSInSAR technology, which chooses either non-local (NL) or minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…2) shows that the pixels excluded by the intensity deviation threshold are basically located in regions without backscattering or noise; the SHPs obtained by FaSHPS does not distinguish well between noisy and strongly scattering regions and are worse than the BWS test; the SHPs obtained by D I + FaSHPS compensate well for the shortcomings of FaSHPS and do not differ significantly from D I + BWS. Based on the number of SHPs selected, the pixels can be divided into PSs and distributed scatterers [44], [45]. Previous studies and analyses have concluded that the maximum number of SHPs considered as PSs is set to 10 [37], [40].…”
Section: A Pss Selection Results and Analysismentioning
confidence: 99%
“…2) shows that the pixels excluded by the intensity deviation threshold are basically located in regions without backscattering or noise; the SHPs obtained by FaSHPS does not distinguish well between noisy and strongly scattering regions and are worse than the BWS test; the SHPs obtained by D I + FaSHPS compensate well for the shortcomings of FaSHPS and do not differ significantly from D I + BWS. Based on the number of SHPs selected, the pixels can be divided into PSs and distributed scatterers [44], [45]. Previous studies and analyses have concluded that the maximum number of SHPs considered as PSs is set to 10 [37], [40].…”
Section: A Pss Selection Results and Analysismentioning
confidence: 99%
“…2). Conventional time-series InSAR techniques are limited to obtain fine monitoring results in target areas, while DS-InSAR can increase the spatial density of the measurement points with a large number of randomly distributed scatters to improve the sampling rate effectively [47][48]. It is better suited for specific characteristics of our study area.…”
Section: B Bayesian Inversionmentioning
confidence: 99%
“…Due to the high vegetation coverage in the study area, the traditional PS point selection method is used to achieve better results. This paper uses three-point selection strategies to select PS points to obtain target points with high phase quality and comprehensive coverage, namely, amplitude departure index method, spectral coherence, and phase stability [26,27].…”
Section: Persistent Scatterer Selectionmentioning
confidence: 99%